Computational Psychometrics Meets Hollywood: The Complexity in Emotional Storytelling - Cipresso, Pietro; Riva, Giuseppe (Frontiers in Psychology, 2016)
Expressions of emotions are pervasive in media, especially in movies. In this article, we focus on the emotional relationships of movie characters in narrative thought and emotional storytelling. Several studies examine emotion elicitation through movies, but there is a gap in scientific literature and in the practice to quantitatively consider emotions among the characters of a movie story, which in turn provide the basis of spectator emotion elicitation. Some might argument that the ultimate purpose of a movie is to elicit emotions in the viewers; however, we are highlighting that the path to emotional stimulation entails emotions among the characters composing a narrative and manipulating to enable the effective elicitation of viewers’ emotions. Here we provided and tested an effective quantitative method for analyzing these relationships in emotional networks, which allow for a clear understanding of the effects of story changes on movie perceptions and pleasantness.